Remodel Troli Industri Menggunakan Metode Weighted Properties Dan Analisis Antropometri Untuk Stasiun Pengisian Dan Pengangkutan Bulk Elpiji - lili rasyidi; Utami Wahyuningsih; Victor Assani Desiawan; Muhammad Yusuf Habibie (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2026)
At the Liquefied Petroleum Gas Filling and Transportation Station (SPBE), trolleys serve as an essential means of transport for moving LPG cylinders. These trolleys play a crucial role in facilitating the handling and movement of cylinders throughout the operational process—from the filling station to the distribution area. However, conventional industrial trolley designs typically use heavy metal materials, which lead to several issues affecting operational efficiency and worker well-being. This study aims to redesign the industrial trolley used at SPBE stations by focusing on the use of lighter materials without compromising mechanical strength. The Weighted Properties Analysis (WPA) method was employed to evaluate various materials based on criteria such as tensile strength, corrosion resistance, lightweight characteristics, cost, and availability. The analysis results indicate that Carbon Fiber Reinforced Polymer (CFRP) is the most suitable material, offering advantages in low weight, high tensile strength, and excellent corrosion resistance. Furthermore, anthropometric data of workers were integrated into the design process to ensure an ergonomic and comfortable trolley that minimizes the risk of injury. The implementation of the proposed trolley design is expected to enhance operational efficiency, reduce workers’ physical load, and support environmental sustainability through the use of durable materials.